2020
DOI: 10.29309/tpmj/2019.27.01.4006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors and the factors related to it among madrassa students in district Sialkot.

Abstract: Objectives: Refractive errors (RE) comprise visual impairment arising from the decreased ability of eye to focus light on retina that has become one of the most common problems among school going children and is the second leading cause of treatable blindness among them.1 RE remains unquantified in Pakistan, especially among madrassa students who are further neglected due to lack of school health services. Keeping this in mind the following study was conducted to find the prevalence of RE among Madrassa studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The theme of eye care pathways encompassed 38 studies 6,108–142,144,149 and 9 other relevant documents 15,107,143,145–148,150,151 and overlaped considerably with the other themes. This theme directly relates back to our research question where we aim to explore the evidence surrounding eye care pathways in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The theme of eye care pathways encompassed 38 studies 6,108–142,144,149 and 9 other relevant documents 15,107,143,145–148,150,151 and overlaped considerably with the other themes. This theme directly relates back to our research question where we aim to explore the evidence surrounding eye care pathways in Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies under this theme reported on screening programmes 108–110,112,114–117,119,127–130,132,134–141 . Papers reporting on the prevalence of DR in Pakistan have expressed the need for organised and consistent DR screening programmes 111,112,114,121,125,128,130,135,143,151 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations